Rethinking Military History - Black, Jeremy (Taylor and Francis, 2004)
Rethinking Military History is a bold new 'thought book' that reconsiders military history at the beginning of the twenty-first century. The chapters provide a valuable and concise survey of the main themes in the study of military history from 1500 to the present day as Jeremy Black reveals the main trends in the practice and approach to military history and proposes a new manifesto for the subject to move forward. This must-read study demonstrates the limitations of current approaches, including common generalizations, omissions, and over-simplications. Engaging theoretical discussions, with reference to specific conflicts, suggest how these limitations can be remedied and adapted, whilst incorporating contributions from other disciplines. Rethinking Military History is essential reading for all those with an interest in military history, and all who wish to take part in moving the discipline forward. Jeremy Black is Professor of History at the University of Exeter. He is editor of the Routledge series Warfare and History. Preface 1. Introduction 2. The Sound of Guns: Military History Today 3. Redressing Eurocentricism 4. Qualifying Technology 5. Setting Military Objectives 6. 1500-1815 7. 1775-1918 8. 1914-Today 9. Conclusions Selected Bibliography Index ' [this book] is stimulating and thought-provoking. It will be of particular value to serious students of military history, and to those who aspire to write it.' - British Army Review '...essential reading for all those with an interest in military history, and all those who wish to take part in moving the discipline forward.' - USI Journal